Cytokinin and Its Key Role to Enrich the Plant Nutrients and Growth Under Adverse Conditions-An Update - Prasad, Ravindra (Frontiers in Genetics, 2022)
Among the field crops, wheat is regarded as one of the most paramount cereal crops because it is widely grown, consumed as food across the world, and also known as the staple food for nearly 35 per cent of the world population. However, it is threatened by spot blotch disease causing considerable yield loss, with existing genotypes lacking the resistance and the necessary nutrients. Cytokinins (CKs) are key phytohormones that not only regulate the plant growth/development but also play an important role during stress and in the nutrient metabolic pathway of crop plants. Deficiency of important nutrients like zinc, iron, and vitamin A causes irreparable damage to the body, pressing the need to increase the accumulation of such micronutrients in the edible parts of the plant. Crop bio-fortification is one of the emerging approaches through which the quantities of these nutrients could be increased to an advisable amount. Cytokinin is observed to have a pivotal role in managing environmental stress/climate change and defense systems of plants, and apart from this, it is also found that it has an impact over Zn accumulation in cereal crops. Manipulation of the cytokine dehydrogenase (CKX) enzyme that degrades cytokinin could affect the yield, root growth, and important nutrients. Several instances revealed that an increment in the contents of Zn, S, Fe, and Mn in the seeds of cereals is a reflection of increasing the activity of CKX enzyme resulting the enhancement of the root system which not only helps in the absorption of water in a drought prone area but is also beneficial for scavenging nutrients to the deeper ends of the soil. Exploring micronutrients from the lithosphere via the root system helps in the uptake of the micronutrients and transporting them via the vascular system to the sink of crop plants, therefore, identification and incorporation of CKs/CKX linked gene(s) into targeted crop plants, exploring a bio-fortification approach including CRISPR-Cas9 through conventional and molecular breeding approaches could be the most paramount job for improving the important traits and stress management in order to enhance the plant growth, productivity, and nutritional value of the wheat crops, which would be useful for mankind.